Structural Determinants of Job Satisfaction: The Mutual Influences of Compensation Management and Employees’ Motivation - Adeoye, Abayomi Olarewaju; Atiku, Sulaiman Olusegun; Fields, Ziska (Journal of Economics and Behavioral Studies, 2016)
The importance of job satisfaction as an antecedent to employees’ productivity and firm outcomes cannot be overrated in the world of business, especially in the service industry. This paper adds to the understanding of job satisfaction in insurance business by investigating the structural causes of task fulfilment. The mutual influences of compensation administration and employees’ motivation on job satisfaction was assessed using multivariate analysis. This research embraced a quantitative method and 212 employees were drawn using a convenience sampling technique. Three propositions were tested employing inferential statistical analyses run through SPSS statistics version 23 and SPSS Analysis of Moment Structures (AMOS) version 23. AMOS was used to structurally determine job satisfaction through structural equation modelling (SEM). SPSS statistics version 23 was instrumental in assessing the psychometric properties via exploratory factor analysis and Cronbach’s alpha coefficients. The results indicate a substantial affiliation between reward administration and motivation. Statistically, this study found that compensation management exerts more direct influence on employees’ job satisfaction than the indirect tie through motivation. There may be a need to redesign human resource practices in the industry to improve the degree of employees’ gratification and duty fulfilment.